Miniaturized 28-GHz Packaged Bandpass Filter With High Selectivity and Wide Stopband Using Multilayer PCB Technology - Rao, Yunbo; Qian, Huizhen Jenny; Zhou, Jie; Dong, Yuandan; Luo, Xun (IEEE microwave and wireless components letters, 2022)
In this letter, a packaged bandpass filter (BPF) with a compact size of 1.5 × 1.5 × 0.315 mm 3 operating at 28 GHz is proposed. This BPF is implemented based on a multilayers printed circuit board (PCB) fabrication process with ultra-thin substrate. With the packaged configuration, the filter can not only reduce the circuit size and component insertion loss, but also eliminate the effect of electromagnetic (EM) radiation. To verify the mechanisms mentioned above, a packaged millimeter-wave (mm-wave) BPF with three transmission zeros is designed and fabricated. The measured results show that the proposed BPF has the merits of low insertion loss, high selectivity, and compact size. Meanwhile, this BPF can suppress harmonics with a rejection level of more than 24 dB up to 110 GHz. With these merits, the proposed BPF is attractive for 5G mm-wave application.